Effect of step-heating on microstructure and mechanical properties of linear low density polyethylene/multi-walled carbon nanotube composites prepared via melt mixing process - Samor Boonphan (2018)
Step-heating (single-and four-step heating) was used in the melt-mixing preparation of linear low density polyethylene (LLDPE)/multi-walled carbon nanotube (MWNT) composites. The MWNT in the composites were used at volume fractions of 0, 1, 3, 5, and 10 vol% (four-step heating), and 0, 1, 3, and 5 vol% (single-step heating). The effects of the heating steps on the microstructure of the LLDPE/MWNT composites were studied. An ultimate tensile testing machine and an impact testing machine were used to characterize the mechanical properties of the composites. The sample prepared using four-step heating had a lower porosity than the sample prepared using single-step heating. The sample with 3 vol% MWNT that was prepared using four-step heating had tensile strength, elastic modulus, and impact strength values that were higher than those of the other samples. © (2014) Trans Tech Publications, Switzerland.